Outcome Analysis of Percutaneous Vertebroplasty in Osteoporotic Compression Fractures - Suvarn Gupta; Tejas Sadavarte; Shraddha Singhania; Vasant Gawande (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Osteoporotic compression fracture of vertebra are very commonly occurring with increasing age. Pain and deformity are most common features. Vertebral augmentation procedures like percutaneous vertebroplasty is a common surgical modality used for osteoporotic compression fractures. Materials and Methods: This prospective observational study was conducted on 36 patients of vertebral compression fracture that underwent percutaneous vertebroplasty in Datta Meghe Medical College in association with Jawaharlal Nehru Medical College. A thorough clinical assessment including physical, neurological, and systemic examination was carried out before taking up patients for percutaneous vertebroplasty. Bony Tenderness at fracture site was examined. Results: This study was conducted in 36 patients of vertebral compression fractures at our institute from January 2019 to January 2020. In our study, out of 36 patients, 24 (66.6%) were females and 18 (33.3%) were males. The mean age was 56.5 ± 6.2 SD years. D12 vertebral fracture was most commonly involved vertebra. The VAS score was used to assess pre and post procedure improvement. The mean pre-operative score 7.4 ± 1.1 SD which reduced to 2.2 ± 0.8 SD at 1 month followup and 2.1 ± 0.5 SD at 1 year follow up. There was significant reduction in pain score post operatively when compared with pre-operative scoring (p value < 0.01). Conclusion: On the basis of this study, we concluded that vertebroplasty is a safe, cost-effective, and pain relieving treatment option available for geriatric patient with osteoporotic vertebral compression fractures which are not relieved by conservative management.